URGENSI PENANGGULANGAN SAMPAH DENGAN ANALISIS SIKAP APATIS MASYARAKAT TERHADAP KESEHATAN LINGKUNGAN DI KOTA SINTANG - Purnomo, Sapto; Ananda, Agnes Sophia; Anjeli, Krisfina (JURNAL PEKAN : Jurnal Pendidikan Kewarganegaraan, 2024)
This research aims to explore the urgency of dealing with waste in Sintang City with a focus on analyzing community apathy towards environmental health. Waste is a serious problem that threatens environmental sustainability, public health and the ecosystem as a whole. Community apathy towards the waste problem can be a major obstacle in mitigation efforts. This research method uses a qualitative and quantitative approach, involving surveys, interviews and data analysis. Respondents were taken from various levels of society in Sintang City. Analysis of people's apathy towards waste was carried out to identify factors that influence ignorance towards environmental health.The research results show that the majority of people in Sintang City have a high level of apathy towards the waste problem. Factors such as a lack of understanding of environmental health impacts, a lack of awareness of personal responsibility, and uncertainty regarding waste management are the main causes of apathy. In this context, education and outreach programs need to be improved to increase public understanding of the urgency of dealing with waste and its impact on environmental health. This research makes an important contribution in making interested parties, including the government and non-governmental organizations, aware of the urgency of handling the waste problem in Sintang City. Joint efforts from various parties are needed to change apathy into awareness and real action in maintaining environmental health.Â Keyword : apathy, environmental healthÂ